WHAT DOES EMOTION TEACH US ABOUT SELF-DECEPTION? AFFECTIVE NEUROSCIENCE IN SUPPORT OF NON-INTENTIONALISM - Lauria, Federico; Preissmann, Delphine (Les ateliers de l'éthique / The Ethics Forum, 2018)
Intuitively, affect plays an indispensable role in self-deception’s dynamic. Call this view “affectivism.” Investigating affectivism matters, as affectivists argue that this conception favours the non-intentionalist approach to self-deception and offers a unified account of straight and twisted self-deception. However, this line of argument has not been scrutinized in detail, and there are reasons to doubt it. Does affectivism fulfill its promises of non-intentionalism and unity? We argue that it does, as long as affect’s role in self-deception lies in affective filters—that is, in evaluation of information in light of one’s concerns (the affective-filter view). We develop this conception by taking into consideration the underlying mechanisms governing self-deception, particularly the neurobiological mechanisms of somatic markers and dopamine regulation. Shifting the discussion to this level can fulfill the affectivist aspirations, as this approach clearly favours non-intentionalism and offers a unified account of self-deception. We support this claim by criticizing the main alternative affectivist account—namely, the views that self-deception functions to reduce anxiety or is motivated by anxiety. Describing self-deception’s dynamic does not require intention; affect is sufficient if we use the insights of neuroscience and the psychology of affective bias to examine this issue. In this way, affectivism can fulfill its promises